2011
DOI: 10.1002/pro.742
|View full text |Cite
|
Sign up to set email alerts
|

Comparative structural and functional characterization of putative protein effectors belonging to the PcF toxin family from Phytophthora spp

Abstract: The PcF Toxin Family (Pfam 09461) includes the characterized phytotoxic protein PcF from Phytophthora cactorum, as well as several predicted protein effectors from other Phytophthora species recently identified by comparative genomics. Here we provide first evidence that such 'putatives', recombinantly expressed in bacteria and purified to homogeneity, similarly to PcF, can trigger defense-related responses on tomato, that is leaf withering and phenylalanine ammonia lyase induction, although with various degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
(67 reference statements)
0
24
0
Order By: Relevance
“…The related PcF (Phytophthora cactorum factor) and Scr (secreted cysteine-rich) toxin families are specific to oomycetes and show much greater heterogeneity among species (39,59,69,116). The numbers of PcF/Scr family genes in Phytophthora and Pythium genomes are highly heterogeneous (39,55,69,116).…”
Section: Extracellular Toxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The related PcF (Phytophthora cactorum factor) and Scr (secreted cysteine-rich) toxin families are specific to oomycetes and show much greater heterogeneity among species (39,59,69,116). The numbers of PcF/Scr family genes in Phytophthora and Pythium genomes are highly heterogeneous (39,55,69,116).…”
Section: Extracellular Toxinsmentioning
confidence: 99%
“…The numbers of PcF/Scr family genes in Phytophthora and Pythium genomes are highly heterogeneous (39,55,69,116). The PcF subfamily is expanded in P. sojae (16 genes), and the Scr family is expanded in P. infestans (11 genes), whereas P. ramorum and Py.…”
Section: Extracellular Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCD induced by phytotoxins is thought to play a central role in providing a source of nutrition for necrotrophic and hemibiotrophic pathogens (Dou and Zhou, ; Mott et al ., ). However, such a response caused by different PcF/SCR effectors shows various degrees of effectiveness (Orsomando et al ., ). In our case, we observed no changes visible to the naked eye when some of the PcF/SCRs, e.g.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that PcF may mimic the effects of a plant signalling protein because it seemingly has structural homology to the pollen protein Ole-e6 with allergenic activity (Nicastro et al, 2009). Oomycetic SCR proteins can be related to PcF mainly on the basis of their conserved sequences, cysteine patterns and N-terminal secretory signals (Bos et al, 2003;Orsomando et al, 2011). The expansion of PcF/SCR gene families in oomycetes has been noted in whole-genome analyses and the size of the family in several species, such as P. infestans (n = 16), P. sojae (n = 19), P. ramorum (n = 4), Pythium ultimum (n = 3) and Hyaloperonospora arabidopsidis (n = 2), has been estimated through annotation (Baxter et al, 2010;Haas et al, 2009;Lévesque et al, 2010;Tyler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%